2018
DOI: 10.1007/s10334-018-0703-y
|View full text |Cite|
|
Sign up to set email alerts
|

3D SASHA myocardial T1 mapping with high accuracy and improved precision

Abstract: The precision of 3D SASHA myocardial T1 mapping was substantially improved using a 3D Beltrami regularization based denoising technique and was similar to that of 2D MOLLI T1 mapping, while preserving the higher accuracy and whole-heart coverage of 3D SASHA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…SENSE reconstruction was performed for both non‐motion‐corrected and motion‐corrected 3D SASHA data sets. A denoising method was applied to the T 1 ‐weighted images of both the 2D and 3D SASHA acquisitions before parametric fitting to reduce the noise and improve both image quality and T 1 precision of the T 1 maps . A 3‐parameter fitting model was then used to reconstruct the T 1 maps offline for the 2 data sets with a pixel‐wise fitting approach.…”
Section: Methodsmentioning
confidence: 99%
“…SENSE reconstruction was performed for both non‐motion‐corrected and motion‐corrected 3D SASHA data sets. A denoising method was applied to the T 1 ‐weighted images of both the 2D and 3D SASHA acquisitions before parametric fitting to reduce the noise and improve both image quality and T 1 precision of the T 1 maps . A 3‐parameter fitting model was then used to reconstruct the T 1 maps offline for the 2 data sets with a pixel‐wise fitting approach.…”
Section: Methodsmentioning
confidence: 99%
“…In order to achieve high precision in spite of the reduced number of saturation recovery time points, we propose to apply a novel 3D Beltrami denoising technique to the T1-weighted images prior to the T1 fitting. The Beltrami framework for image denoising and enhancement was introduced for 2D natural images by Sochen, Kimmel and Malladi (16), proposed for 2D myocardial T1 mapping denoising by Bustin et al (16), and have been recently extended to 3D T1 mapping denoising (17). The Beltrami regularization allows to preserve the edges, while reducing the noise of the images without introducing staircasing artefacts (18) .…”
Section: D Denoisingmentioning
confidence: 99%
“…For both prospective and retrospective studies, the 3D SASHA T1 map with nine images along the recovery curve was considered as the reference standard. 3D SASHA with nine images along the recovery curve has been previously compared against 2D MOLLI showing excellent agreement in terms of accuracy(17).…”
mentioning
confidence: 99%
“…Recently, we demonstrated the feasibility of a free-breathing 3D SASHA [10] imaging technique, which allows to provide wholeheart coverage with higher signal-to-noise ratio (SNR) and image resolution than with conventional 2D approaches. We have also demonstrated that the precision of 3D SASHA can be improved, without affecting the T1 accuracy, using a post-processing 3D denoising technique based on Beltrami regularization applied directly on the T1-weighted images [11]. The acquisition time of the 3D SASHA sequence is considerably longer than a breath-hold (in the order of 12 min), thus 1D diaphragmatic navigator gating (and tracking) was employed to enable 3D free-breathing T1 mapping [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we propose to accelerate the 3D SASHA acquisition by reducing the number of the T1-weighted images acquired along the saturation recovery curve. To overcome the expected loss in accuracy and precision due to the reduced number of T1-weighted images acquired, we use the 3D denoising technique based on Beltrami regularization applied directly to the T1-weighted images prior to T1 fitting (as is [11]), enabling accurate and precise 3D SASHA T1 mapping from fewer saturation points and thus shorter scan times. The proposed approach was tested on a standardized T1 phantom, 10 healthy subjects with retrospectively reduced number of T1-weighted images, 10 healthy subjects with prospectively varied number of T1-weighted images and three patients with suspected cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%